EKSISTENSI AKUNTANSI DALAM ISLAM - Delima Sari Lubis (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Abstract Accounting in Islam known as muhasabah. Muhasabah could mean bookkeeping, calculation , debat , and imbalans in Islam known as muḥāsabah. By the definition of sharia accounting is a collection of legal basis and a permanent standard, which is inferred from the sources of Islamic law and is used as a rule by an accountant in his work, both in accounting, analysis, measurement, presentation , and explanation, and became a foothold in explain an event or events. Based on the known history of the concept of sharia accounting that has existed much earlier than conventional accounting concepts. Based on the known history of the concept of sharia accounting that has existed much earlier than conventional accounting concepts . Kata Kunci : Accounting, muhasabah